Allometric response of two sugarcane cultivars for panela to foliar fertilization in the nursery - Deantonio-Florido, Leidy Yibeth (2021)
Introduction. In Colombia, the panela agribusiness stands out for its social, economic, and food security contributions; however it demands technological improvements in the management of the fertilization of sugarcane cultivars. Objective. To determine the effect of foliar fertilization in the nursery stage on the growth parameters of two sugarcane cultivars for the production of panela. Materials and methods. The experiment was carried out in 2018 at the Corporacion Colombiana de Investigacion Agropecuria (AGROSAVIA) Cimpa headquarters. A completely randomized experimental design was established to evaluate in cultivars CC 93-7510 and CC 93-7711 the growth of plants exposed to three foliar fertilization treatments: (1) nitrogen source, (2) source with macro and micronutrients (complete), (3) mixture of sources, and an absolute control. Allometric variables (height, diameter, number of leaves, and root dry weight) and growth indices were recorded over time; with the former, generalized linear mixed models and Poisson models were constructed, and with the indices, a uni and multivariate analysis of variance. Results. The evaluation factors (fertilization and time) presented significant effects (p≤0.05) on the allometric variables in the two cultivars compared to the control (without fertilization); while the growth indices presented statistically significant differences due to the effect of the fertilization sources. The CC 93-7510 sugarcane plants fertilized with the mixture of complete and nitrogen sources presented greater height and diameter of the stems, number of leaves, and dry weight of roots. As for the CC 93-7711 sugarcane plants fertilized with the complete source, they showed greater diameter of the stem and accumulation of dry weight of roots. Conclusions. Foliar fertilization in sugarcane plants of both cultivars allowed greater allometric development in less time.